2019
DOI: 10.1002/term.2826
|View full text |Cite
|
Sign up to set email alerts
|

Coculture with monocytes/macrophages modulates osteogenic differentiation of adipose‐derived mesenchymal stromal cells on poly(lactic‐co‐glycolic) acid/polycaprolactone scaffolds

Abstract: The effects of immune cells, in particular macrophages, on the behaviour of mesenchymal stromal cells (MSCs) have recently gained much attention for MSCs‐based tissue‐engineered constructs. This study aimed to evaluate the effect of monocytes/macrophages on the osteogenic differentiation of adipose‐derived mesenchymal stromal cells (ADMSCs) in three‐dimensional (3D) cocultures. For this, we cocultured THP‐1 monocytes, M1 macrophages, or M2 macrophages with ADMSCs on 3D poly(lactic‐co‐glycolic) acid (PLGA)/poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…There have been attempts by other groups to incorporate monocytes or macrophages into 3D tissue systems. [22][23][24][25][26][27] Nevertheless, the results are controversial; while some groups have shown a similar synergistic effect in bone formation when hMSCs are co-cultured with macrophages, [25][26][27] others have observed the opposite effect of macrophages on bone formation. [22][23][24] It is important to acknowledge that these co-culture studies differ from the current one in cell species type (murine vs. human), monocyte or macrophage type, hMSC origin, and scaffold material.…”
Section: Discussionmentioning
confidence: 99%
“…There have been attempts by other groups to incorporate monocytes or macrophages into 3D tissue systems. [22][23][24][25][26][27] Nevertheless, the results are controversial; while some groups have shown a similar synergistic effect in bone formation when hMSCs are co-cultured with macrophages, [25][26][27] others have observed the opposite effect of macrophages on bone formation. [22][23][24] It is important to acknowledge that these co-culture studies differ from the current one in cell species type (murine vs. human), monocyte or macrophage type, hMSC origin, and scaffold material.…”
Section: Discussionmentioning
confidence: 99%
“…Both subtypes of macrophages inhibited the osteogenic differentiation of MSCs, with M2 macrophages exhibiting an even stronger inhibiting effect than M1 macrophages. N-cadherin was considered the mediator between macrophages and MSCs responsible for the inhibition of osteogenesis [60]. Another study published from the same team followed the same (3D) coculture methods but with poly(lactic-co-glycolic) acid/polycaprolactone scaffolds demonstrating similar results.…”
Section: Bone Regeneration Inhibited By Macrophagesmentioning
confidence: 95%
“…Guihard et al (2012) found that conditioned media from human monocytes stimulated with LPS or TLR ligands enhanced bone formation by human bone marrow MSCs. Enhanced osteogenesis was also observed by several groups, they demonstrated that M1 macrophages promote osteogenesis in MSCs via the COX-2-PGE2 pathway (Guihard et al, 2012;Lu et al, 2017;Zhang et al, 2017;Nathan et al, 2019;Tang et al, 2019). Recently, the Shi group reported that macrophage-derived supernatants can inhibit the adipogenic differentiation of human adiposederived mesenchymal stem cells (hADSCs) in vitro, irrespective of the polarization status (M0, M1, or M2 macrophages) (Ma et al, 2020).…”
Section: Effect Of Macrophage On Mscmentioning
confidence: 80%